A general equilibrium world with price and quantity signals: A duality approach - Bodo Hilgers; Ulrich Wacker (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1999)
Our contribution offers a methodological exhibition of general equilibrium models with price and quantity signals. By the application of optimal value functions the household as well as the firm behaviour is modelled. The concepts of virtual prices and virtual quantities allow us to express constrained by unconstrained functions. Starting with these optimal value functions, behavioral functions describing the market coordination of supply and demand by price and quantity signals can be derived. We will show that by means of our method we can derive any general equilibrium model characterized by price and quantity signals with an arbitrary number of goods and factor markets. Furthermore, our method allows to construct a fully integrated general equilibrium framework not only with a finite number of goods and factor markets characterized by quantity constraints but also with unconstrained goods and factor markets.
Keywords: 330